Structural and phase evolution in U3Si2 during steam corrosion. (1st August 2022) - Liu, Jiatu; Burr, Patrick A.; White, Joshua T.; Peterson, Vanessa K.; Dayal, Pranesh; Baldwin, Christopher; Wakeham, Deborah; Gregg, Daniel J.; Sooby, Elizabeth S.; Obbard, Edward G.
Abstract: U3 Si2 nuclear fuel is corroded in deuterated steam with in situ neutron diffraction. Density functional theory is coupled with rigorous thermodynamic description of the hydride including gas/solid entropy contributions. H absorbs in the 2 b interstitial site of U3 Si2 Hx and moves to 8 j for x ≥ 0.5. Hydriding forces lattice expansion and change in a/c ratio linked to site preference. Rietveld refinement tracks the corrosion reactions at 350–500 °C and preference for the 8 j site. Above 375 °C, formation of UO2, U3 Si5 and USi3 take place in the grain boundaries and bulk. Hydriding occurs in bulk and precedes other reactions. Graphical Abstract: ga1 Highlights: In situ neutron diffraction measures U3 Si2 corrosion in deuterated steam. Rigorous thermodynamic description of hydride using key entropy contributions. H absorption at 2 b interstitial site of U3 Si2 Hx, moves to 8 j site for x ≥ 0.5. From 350 °C, U3 Si2 Hx fragmented by 1–2% anisotropic lattice expansion. From 375 °C, UO2, U3 Si5 and USi3 form in bulk and in grain boundaries.